If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5x+24)+2=3x+24
We move all terms to the left:
(5x+24)+2-(3x+24)=0
We get rid of parentheses
5x-3x+24-24+2=0
We add all the numbers together, and all the variables
2x+2=0
We move all terms containing x to the left, all other terms to the right
2x=-2
x=-2/2
x=-1
| 6(u-1)+8=32 | | 6(u-1)+8=20 | | 2(3x+4)=5(x−2) | | u+3(u+4)=20 | | n+5=73-8 | | 45=32+5x | | 7(8+5x)=91 | | 3y+2.5=13 | | 4^xx4^-9=1 | | 4(5x+7)=268 | | 3x*40=236 | | 3x×40=236 | | 3(-2x+10)=66 | | 6(7x+6)=540 | | -3(3x-8)=-21 | | -4(6x+5)=124 | | Y=3(x+3)(x-2) | | -2(4x+3)=-6 | | 4(6-7x)=-288 | | -4(8+x)=-76 | | 24=-2(b-3)=8 | | 36v^2+24v=0 | | -b-5b=b | | -6(-9-2x)=198 | | -36x+8x=-20-1 | | 15.3w+2.5=5.7w+31.3 | | .25(10x+30)=6x+7 | | X+5^0.5*(20^2+(100-x)^2)^0.5=0 | | 8x=12x+40 | | 5(2)+x=15 | | 6.8b-3.7=30.3 | | 4/5m-5=2/5m+3 |